CRITICAL INCIDENT STRATEGY: IMPROVING MOTIVATION AND LEARNING OUTCOMES OF ISLAMIC EDUCATION STUDENTS IN PATTANAKARNSUKSA SCHOOL SONGKHLA THAILAND - Fareezee Rattanayium; Asrori Asrori; Rusman Rusman (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Critical Incident Strategy: Increasing Motivation and Learning Outcomes of Islamic Education Students is a strategic issue to be studied in depth through the research process. The method used in this research is PTK with 33 students as subjects. This research consists of 2 cycles in it with motivational targets in cycle 1 and cycle 2, namely student motivation in the medium and high categories, while on learning outcomes, namely the minimum class criterion value in cycle 1 is 65, cycle 2 is 75. The results of the study show, with critical incident strategy, obtained motivation and learning outcomes have increased. The results in the first cycle were 24.24% of students who had a very high category, in the second cycle it increased by 84.85%, while in the high category it became 15.15%. The increase in learning outcomes in the cognitive aspect can be seen from the percentage of class completeness in the initial conditions of 9%, the first cycle was 45.45% and in the second cycle, it increased to 87.87%, while the increase in the class average value from the initial conditions was 58.00 Cycle I 71.67 in cycle II 76.39. Based on the results of the study it can be concluded that the critical incident strategy "increases" motivation and student learning outcomes. The implication of research on Critical Incident Strategy: Increasing Motivation and Learning Outcomes of Islamic Religious Education Students is to determine learning strategies to improve learning outcomes which can be seen from their learning motivation